2003
DOI: 10.1038/sj.bjc.6600959
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evolution of tumour cells after the generation of double-strand DNA breaks

Abstract: In vitro, the ratio of single-to double-strand DNA breaks (DSB) and their absolute values determine the cell death pathway. The consequences of the generation of various numbers of DSB generated in vivo in tumour cells have been analysed in two different experimental tumour models. Synchronisation of DSB generation and control of their number have been achieved using different doses of bleomycin (BLM) and tumour cell permeabilisation by means of locally delivered electric pulses. According to BLM dose, differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…It has been shown that ECT induces a recruitment of mononuclear leucocytes within and around the treated metastatic lesions [17]. While the nature of these infiltrate in mice has been unravelled [18], in humans it has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ECT induces a recruitment of mononuclear leucocytes within and around the treated metastatic lesions [17]. While the nature of these infiltrate in mice has been unravelled [18], in humans it has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…B16F0 melanoma is poorly or non-immunogenic and recidivates after removal. 21,22 MC-C tumor, on the other hand, has the characteristics of a non-infiltrating slow growing fibrosarcoma. 7,23 It is highly immunogenic and, unlike B16F0 melanoma, it never recidivates after removal.…”
Section: Methodsmentioning
confidence: 99%
“…As described in this article, intratumoral injections of bleomycin were carried out in our study. This regimen tends to give a high number of molecules internalized, leading to necrosis of both tumor tissue and normal tissue (47). From clinical studies, we know that normal tissue may be spared whereas efficient tumor cell kill is obtained with i.v.…”
Section: Electrochemotherapy Of Brain Tumorsmentioning
confidence: 99%